Nanoscale kinetic segregation of TCR and CD45 in engaged microvilli facilitates early T cell activation - Yair Razvag (Nature Portfolio, 2018)
T cell activation is critically controlled by T cell receptor (TCR) signalling. Here the authors show, using live cell imaging, atomic force microscopy and modelling simulation, a prompt separation of TCR and CD45 that negatively correlates with TCR activation, supporting a refined kinetic segregation model of TCR signalling.